Francoist Repression against Women - Ranz Alonso, Eduardo (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
The situation of women, in relation to historical periods, has always been that of survival. After the beginning of the Civil War, and the involution in rights, republican women suffered a double victimization, the loss of rights and loved ones, and repression of their honor, their privacy, or their body being outraged, raped, imprisoned, vexed , “Strolled”, shaved, forced to ingest castor oil, murdered, and even, group shooting, as was the case of the 13 roses. Slave labor suffered by them, sometimes, in harder conditions than that of men.For the coup side, they were dehumanized or killed without responsibility for the murderer, and on the Republican side, they ended their days without the deserved recognition of the comrades in struggle or resistance. Its situation in the subsequent dictatorship was reduced to a minority, with the cooperation of the Catholic Church.With the arrival of democracy, the conquests of social rights were many, not so, the advances in feminism. Proof of this is that it will not be until April 2004, when parity in Spain is known in the Council of Ministers.The methodology of the investigation, part of the analysis of the sources or scientific literature, divided into six large blocks: Law of Historical Memory; documentation of the commanders of the Civil Guard, and General Archive of the Ministry of the Interior; jurisprudence of national and European Courts and Tribunals; the “Valientes” books, by El País journalist Natalia Junquera; “San Marcos. The unknown concentration camp “, by journalists López Alonso and Gallo Roncero; as well as an interview with President José Luis Rodríguez Zapatero, for the doctoral thesis of the author of this candidacy, “legal processes in historical memory”.The heroines were them, because they survived.
Keywords: republicans rights; recognition; repression; murdered